2006
DOI: 10.5741/gems.42.1.4
|View full text |Cite
|
Sign up to set email alerts
|

"Paraíba"-Type Copper-Bearing Tourmaline from Brazil, Nigeria, and Mozambique: Chemical Fingerprinting by LA-ICP-MS

Abstract: Gem-quality bright blue to green "Paraíba"-type Cu-bearing tourmaline is now known from deposits in Africa (Nigeria and Mozambique), in addition to three commercial localities in Brazil (in Paraíba and Rio Grande do Norte States). Stones from these new localities have been mixed into parcels from the original Brazilian Paraíba occurrence. The Nigerian and Mozambique tourmalines that show saturated blue-to-green colors cannot be distinguished from the Brazilian material by standard gemological testing or on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Any single pair of certain elements is insufficient to determine the geographic origin, but the combination of these elemental discriminators provides a robust tool for origin determination. In general, the results presented here are comparable to those in previous studies (e.g., Abduriyim et al, 2006;Peretti et al, 2009;Okrusch et al, 2016). Using GIA's reference data, four selected case studies for origin determination are shown in box A.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Any single pair of certain elements is insufficient to determine the geographic origin, but the combination of these elemental discriminators provides a robust tool for origin determination. In general, the results presented here are comparable to those in previous studies (e.g., Abduriyim et al, 2006;Peretti et al, 2009;Okrusch et al, 2016). Using GIA's reference data, four selected case studies for origin determination are shown in box A.…”
supporting
confidence: 89%
“…Quantitative chemical analyses of minor and trace elements have been collected and presented herein for Brazilian, Nigerian, and Mozambican material as used for locality determination (e.g., Shigley et al, 2001;Breeding et al, 2007;Laurs et al, 2008). Com- parative studies of chemical data have also been carried out and discussed for the purpose of origin determination by several authors (Abduriyim et al, 2006;Peretti et al, 2009;Okrusch et al, 2016). For GIA's lab service of Paraíba tourmaline origin determination, we have established an analytical and calculation protocol that utilizes major, minor, and trace element data obtained by LA-ICP-MS on reference samples from known localities.…”
mentioning
confidence: 99%
“…The striking neon-blue "Paraíba tourmaline" invariably is characterized by high Cu contents, with up to 2.32 wt.% CuO (Abduriyim et al 2006, Fritsch et al 1990, Henn & Bank 1990, Shigley et al 2001. In elbaite of other colors, copper is usually below the detection limit or present only in trace amounts (<0.56 wt.% CuO).…”
Section: Major and Trace Elementmentioning
confidence: 97%
“…The chemistry of natural Cu-bearing tourmalines with significant amounts of Bi (up tõ 0.5-0.8 wt % Bi 2 O 3 ) was described by [25][26][27][28]. The highest amount of Bi (~1.5 wt % Bi 2 O 3 ) in Cu-bearing tourmaline was described by [29]. Tourmalines with up to~0.5 wt % Bi 2 O 3 , but without significant amounts of Cu were described by [30] from a granitic pegmatite in Zambia.…”
Section: Introductionmentioning
confidence: 99%